Unveiled: Prototrichalus from the mid-Cretaceous Burmese amber represents a yet oldest record of Ischaliidae Blair, 1920 (Coleoptera: Tenebrionoidea) - Telnov, Dmitry; Kairišs, Kristaps; Triskova, Katerina; Kundrata, Robin (Cretaceous research, 2023)
The genus Prototrichalus Molino-Olmedo, Ferreira, Branham and Ivie, 2020 known from Burmese amber was initially attributed to the family of net-winged beetles (Coleoptera: Lycidae) in the superfamily Elateroidea, and soon after transferred to Tenebrionoidea incertae sedis and compared with Ischalia Pascoe, 1860. Here, we examined additional material of Prototrichalus and confirmed it is the first known Mesozoic subgroup of the family of false fire-coloured beetles (Coleoptera: Ischaliidae) in superfamily Tenebrionoidea. This oldest yet available record of the Ischaliidae suggests their at least Cretaceous origin. A re-defined set of the diagnostic features is provided for the family Ischaliidae to incorporate the unique combination of morphological features of Prototrichalus. One new species, P. jingpo Telnov and Kundrata, sp. nov., is described and compared with its congeners. A key to supraspecific taxa of Ischaliidae and an annotated checklist of extinct species of the family are provided.
Online verfügbar: 30. Juni 2023, Artikelversion: 19. Juli 2023
Gesehen am 05.10.2023